Exploring Inclusive Practices: Accessibility for Students with Disabilities in West Sumatra’s Public Universities - Bashori, Bashori; Kurniawan, Anri; Juniarni, Citra; Mayesti, Indria (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: Persons with disabilities often encounter significant barriers in accessing educational services that are not yet inclusive or disability-friendly. These limitations contribute to systemic discrimination and result in the delivery of inadequate public services. Research Methods: This study adopts a descriptive qualitative case study approach aimed at identifying both physical and non-physical accessibility services, as well as the key factors influencing their availability at a state Islamic university in West Sumatera, Indonesia. Finding/Results:  The findings indicate that: (1) non-physical accessibility services—particularly in the areas of information access, policy and specialized support—are still underdeveloped; (2) physical accessibility features, such as disability-friendly toilets and ramps, are available but remain very limited; and (3) the availability of such services is shaped by several crucial factors, including institutional commitment and awareness, the presence of disability-related data, institutional policies and needs, and the influence of international accreditation standards. These factors collectively serve as the primary drivers in the realization of an inclusive and equitable university environment. Conclusion: The study concludes that accessibility services at UIN Imam Bonjol Padang remain insufficient and recommends enhanced institutional focus on inclusive infrastructure, policy reform, and data management to support students with disabilities effectively.